EXPLORING THE FEEDING PATTERNS OF SIAMANGS: BEHAVIOR AND FOOD PREFERENCES IN ZOO ENVIRONMENTS AND THEIR CONTRIBUTION TO BIOLOGY EDUCATION - Sisilia, Panjaitan Grace; Prihatmo, Guruh; Purba, Laurentia Henrieta Permita Sari (Universitas Lancang Kuning, 2025)
The siamang (Symphalangus syndactylus), an endemic primate of Indonesia, is critically endangered due to hunting and habitat destruction and is now predominantly found in conservation areas. This study aims to analyze the feeding behavior and food preferences of siamangs in the zoo, evaluate the suitability of the ex-situ diet composition compared to their natural diet, and assess its contribution to biology education. The research methods included 480 hours of feeding behaviour observation using scan sampling, descriptive data analysis, and Pearson correlation tests. The results indicate that the siamang's diet in zoos is dominated by fruit (53.88% for males and 56.38% for females), followed by leaves and supplementary foods such as tubers and biscuits. The dietary composition is similar to studies conducted in their natural habitat, although the variety of zoo food is more limited. Adjustments to the feeding menu, such as hanging food at elevated locations and increasing the variety of local fruits, could support the siamangs' natural feeding behaviours. In conclusion, the feeding patterns of siamangs in zoos largely align with their natural behaviour as frugivores, although improvements in feeding methods and dietary variety are needed. The implications of this study emphasize the importance of aligning ex-situ conditions with natural habitats to support animal welfare and conservation programs while also strengthening the role of zoos as centres for education and biodiversity preservation.